Financial Technology : Praktik Pinjaman Online dalam Perspektif Ekonomi Syariah - Ishaq, Maulana; Suselo, Dedi (Universitas Muhammadiyah Metro, 2024)
The development of financial technology gives rise to various conveniences with negative impacts. One form of this convenience is an online loan that provides instant loan transactions. Various online loan applications come with an installment platform with an adjustable time period. This transaction model is in great demand among students as an alternative to financing consumption and education. This study explores students' motivation to use online loan applications and the risks that must be borne. This study uses qualitative descriptive analysis to get in-depth answers from the students. The results of this study indicate that they are interested in and use online loan applications because of the ease of borrowing funds for pocket money and paying tuition fees. However, and states that online loan are allowed, the most important thing in their application is that they do not conflict with sharia principles in the fatwa of the national sharia council no 117/DSN -MUI / IX / 2018.